Makna Q.S. 94 Ayat 5 dan 6 Tinjauan Semantik Toshihiko Izutsu - Idrus Ahmad; Agus Boriri; Masria Atib (Peneliti.net, 2023)
As a specific science, language is used to dissect expressions that require deep meaning (mutasyabihat). Not limited to muhkamat in religious language or denotative in semantics. There have been many verses of the Koran, dissected using the services of linguistics, namely semantics. This time, the author dissects Q.S. 94 verses 5 and 6 which are repeated twice in two verses, using Toshihiko Izutsu's semantic theory approach with three paths of analysis: (1) basic meaning analysis and relational meaning analysis, (2) synchronic and diachronic analysis, and (3) analysis to find weltanschauung or concepts that humans can understand and practice so as to create a Quranic society.